Aryl Hydrocarbon Receptor-Dependent Metabolism Plays a Significant Role in Estrogen-Like Effects of Polycyclic Aromatic Hydrocarbons on Cell Proliferation - Hýžd'alová, Martina; Pivnicka, Jakub; Zapletal, Ondrej; Vázquez-Gómez, Gerardo; Matthews, Jason; Neca, Jirí; Pencíková, Katerina; Machala, Miroslav; Vondrácek, Jan (Toxicological sciences, 2018)
Polycyclic aromatic hydrocarbons (PAHs) are widespread environmental contaminants that interact in a complex manner with both the aryl hydrocarbon receptor (AhR) and estrogen receptors (ER). Their potential endocrine-disrupting activities may depend on both inhibitory AhR-ER cross-talk and on AhR-dependent metabolic production of estrogenic PAH metabolites. Here, we analyzed the impact of AhR on estrogen-like effects of PAHs, such as benzo[a]pyrene (BaP), in particular, on control of cell cycle progression/cell proliferation. Using AhR knockout variant of estrogen-sensitive human breast cancer MCF-7 cells (MCF-7 AhRKO cells), we observed that the AhR-dependent control of cytochrome P450 family 1 (CYP1) expression played a major role in formation of estrogenic BaP metabolites, most notably 3-OH-BaP, which contributed to the ER-dependent induction of cell cycle progression/cell proliferation. Both BaP metabolism and the BaP-induced S-phase transition/cell proliferation were inhibited in MCF-7 AhRKO cells, whereas these cells remained sensitive towards both endogenous estrogen 17β-estradiol or hydroxylated BaP metabolites. BaP was found to increase the activity of ER-dependent luciferase reporter gene in wild-type MCF-7 cells; however, unlike its hydroxylated metabolite, BaP failed to stimulate luciferase activity in MCF-7 AhRKO cells. Similarly, estrogen-like effects of other known estrogenic PAHs, such as benz[a]anthracene or 3-methylcholanthrene, were diminished in MCF-7 AhRKO cells. Ectopic expression of human CYP1A1 and CYP1B1 enzymes partly restored both BaP metabolism and its effects on cell proliferation. Taken together, our data suggest that the AhR-dependent metabolism of PAHs contributes significantly to the impact of PAHs on cell proliferation in estrogen-sensitive cells.
Keywords: polycyklické aromatické uhlovodíky; Cytochrome P-450 CYP1A1; lidé; Plasmids; Cell Culture Techniques; Cell Proliferation; Cytochrome P-450 CYP1B1; Gene Expression; endokrinní disruptory; Genes, Reporter; transfekce; MCF-7 Cells; buněčný cyklus; cytochrom P-450 CYP1A1; Cell Cycle; Humans; plazmidy; reportérové geny; receptory aromatických uhlovodíků; MFC-7 buňky; Polycyclic Aromatic Hydrocarbons; proliferace buněk; Receptors, Aryl Hydrocarbon; cytochrom P450 CYP1B1; genetické vektory; genový knockdown; buněčné kultury; Receptors, Estrogen; Endocrine Disruptors; receptory pro estrogeny; exprese genu; Genetic Vectors; Gene Knockdown Techniques; Transfection